Exploring the Tagasalo Personality and Its Implication as a Localized Personality Scale - Arnel Perez (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
Tagasalo theory hypothesized that every Filipino family has a tagasalo (catcher), a female eldest child who took household roles in early life and eventually expanded to emotional care to the members of the family. In this study, the tagasalo was explored based on the constructed personality scale, Panukat sa Tagasalo Personality (Scale for Tagasalo Personality). There were 27 participants consisting of staff, members of the faculty, field of study heads, and deans who responded to the study. The data in this study were interpreted and analyzed using t-Test: Two-Sample Assuming Unequal Variances for significant differences and regression analysis for significant correlation of the Microsoft Excel. The findings showed that the majority of the participants were Slight tagasalo. Moreover, as regards gender, the male and female participants were found to be significantly different. However, as regards ordinal position, such as firstborn child, later-born child, and others found to be no significant differences, and the majority of the participants as regards to their birth order were Slight tagasalo. In this study, the small number of samples and the use of the non-probability sampling method may threaten the generalizability of the research findings and the representation of the entire population.